Spell checker implementation to analyze the narrative essay of sixth-grade elementary school students in Indonesia - Gipayana, Muhana (Association for Scientific Computing Electrical and Engineering, 2017)
Learning Bahasa Indonesia correctly in terms of writing and reading is needed by students to understand well the language learned in school. Some problems arise when elementary school students still need guidance in writing Indonesian sentences in narratives, that are still lacking the standard or misspelling. Teachers usually read essays from students but it takes a lot for the teacher to learn. This research emerged with the aim of assisting teachers and students in correcting the spelling of the essay that was written so that it would be a perfect and perfect sentence. Applications built using internet technology so students can access the system anywhere. The results show that 87% of students experience spelling errors in writing narrative essay because they are inaccurate to what they write, so the application will provide automatic correction and already implemented in several schools at Malang.